Odpowiedzi

2010-01-02T20:25:11+01:00
S = n² + (n+1)² + (n+2)² = n² +n² +2n + 1 + n² + 4n + 4 =
= 3n² + 6n + 5 = 3n² + 6n + 3 +2 = 3*(n² + 2n +1) + 2
Czyli S = 3*k + 2 co oznacza ,że przy dzieleniu S przez 3
otrzymamy resztę 2.
1 5 1
Najlepsza Odpowiedź!
2010-01-02T20:26:00+01:00
Założenie: n, n+1, n+2 ∈ N - kolejne liczby naturalne

Teza: 1/3 x n²+(n+1)² + (n+2)² =3a+2

1/3 x [n²+n²+2n+1+n²+4n+4]

1/3 x (3n²+6+5)

1/3 x (3n²+6+3+2)

1/3 x (3n²+6+3)+2 <dzielę przez 3>

(n²+2n+1)+2

(n+1)²+2 = 3a+2

Teza zgodna z założeniem.
2010-01-02T20:34:11+01:00
N²+(n+1)²+(n+2)²=n²+n²+2n+1+n²+4n+4=3n²+6n+5
(3n²+6n+5)/3=n²+2n+1 i reszta 2